Usability, Feasibility, and Effect of a Biocueing Intervention in Addition to a Moderated Digital Social Therapy-Platform in Young People With Emerging Mental Health Problems: A Mixed-Method Approach - van Doorn, Marilon; Nijhuis, Laurens A.; Monsanto, Anne; van Amelsvoort, Thérèse; Popma, Arne; Jaspers, Monique W. M.; Noordzij, Matthijs L.; Öry, Ferko G.; Alvarez-Jimenez, Mario; Nieman, Dorien H. (Frontiers in Psychiatry, 2022)
Introduction To optimize treatment, it is of utmost importance to take into account the myriad of biological, social, and psychological changes that young people go through during adolescence which make them more vulnerable for developing mental health problems. Biocueing, a non-invasive method to transform physiological parameters into an observable signal, could strengthen stress- and emotion regulation by cueing physiologically unusual values in daily life. The aim of this study is to investigate the usability, feasibility, and exploratory effect of biocueing in addition to ENgage YOung people earlY (ENYOY), a moderated digital social therapy-platform, in young people with emerging mental health complaints. Methods A user-centred mixed-method design was used. A focus group was conducted to optimize the ENYOY-platform and biocueing intervention. Biocueing was operationalized by a smartwatch and the Sense-IT app. A within-subjects design was used; ten days for all participants ‘biofeedback off’ (control), followed by ten days ‘biofeedback on’ (experimental). Emotional awareness and perceived stress were measured using ecological momentary assessment. Eight individuals participated. User-friendliness, usability, and acceptance were assessed using a qualitative design. Results Findings from the focus group resulted in several adaptations of the biocueing intervention to the ENYOY-platform and vice versa. The average measurement compliance rate was 78.8%. Level-one findings showed different individual effects on perceived stress and emotional awareness. Level-two analyses showed no overall effects on perceived stress (B = -.020, p = .562) and overall positive effects on emotional awareness (B = .030, p = .048) with small effect sizes (Improvement Rate Difference=.05-.35). The intervention was found to be acceptable and showed moderate usability. Participants indicated they experienced improvements in reflection on feelings and changes in behaviour, such as pausing and evaluating the situation. Conclusion These preliminary results show that biocueing could be a promising addition to digital treatment platforms and help young people become more emotionally aware. Improvements should be made regarding the usability and acceptability of the smartwatch, as well as more extensive integration of the biocueing intervention with a digital treatment platform. It would be relevant to gain a better understanding of which individuals would benefit most from an additional biocueing intervention.